Metabolomic profiling of beers: Combining 1H NMR spectroscopy and chemometric approaches to discriminate craft and industrial products. (15th October 2020) - Palmioli, Alessandro; Alberici, Diego; Ciaramelli, Carlotta; Airoldi, Cristina
Highlights: A method for rapid beer metabolites' determination from NMR spectra is described. 1 H NMR combined with chemometric methods discriminates craft and industrial beers. Both untargeted and targeted analyses were effective in affording the separation. The metabolites responsible for the discrimination were identified. Abstract: The authentication and traceability of craft beers is an important issue for both beer consumers and producers. Reliable analytical methods able to identify and discriminate products are needed to protect the craft brew market against fraud and counterfeit. Here, 1 H NMR analysis of 31 beer samples, differing for beer style and brewing method (craft or industrial) was combined with multivariate statistical analysis, following both an untargeted and a targeted approach. NMR-based analysis of beer samples was sped developing a specific protocol enabling the automatic identification and quantification of metabolites in approximately thirty seconds per spectrum. A clear discrimination was achieved by exploiting 1 H NMR analysis and multivariate chemometric methods and the targeted approach identified the metabolites responsible for the segregation. Overall, this study reports an analytical approach addressing beer traceability and is the starting point for the development of a standardized protocol for the discrimination of industrial and craft beers.